Comparison of Several New Energy Vehicles and Gasoline Vehicles During the Same Price Range - Si, Mingyu; Li, Shijie (American Journal of Management, 2022)
Consumers frequently consider the advantages between traditional gasoline vehicles and new energy vehicles. This experiment compared NEVs and traditional gasoline vehicles in aspects of carbon emissions, daily consumption, and value preservation rate. Traditional gasoline vehicles have a higher value preservation rate than new energy vehicles on average. However, NEVs have better environmental protection and money-saving properties. What is more, if the governments and companies use some new energy sources such as nuclear and wind as the electric supply, it will be more environmental-friendly, and help consumers save more money on daily driving. In summary, if consumers do not have plans to sell their cars, it is better for both daily use and environmental protection to buy a new energy vehicle. This experiment can help customers have a reference standard when choosing a car. However, many factors were not considered in this experiment, such as the life of the battery and engine and the impact of the customer's car habits on the car. The experimental results are only for reference.